Scientist and organizer of science - Vladimir Porfirievich Karpov (1870 - 1943). - Gurkin, V. A. (Морфологія / Morphologia / Morfologìâ, 2019)
Karpov in the 1910s - 1920s created a whole school of histologists, which included such scientists as Professor M. Ya. Subbotin (head of the histology department at the Novosibirsk Medical Institute), professor N. L. Gerbilsky (head of the biology department at Leningrad University), professor B. P. Khvatov, creator of the Crimean school of embryologists; professor G.M. Semenov (Samarkand University); Professor N.Kh. Flerov (head of the histology department at the Voronezh Medical University), Professor P.Ya. Lakhovsky (organizer of the histology department at the Kuban Medical Institute, and then at Perm and Gorky Medical Institute). His textbooks and teaching aids on histology have survived multiple reprints. But, unfortunately, not much is known about Karpov himself.